Dinâmica da Produtividade e Eficiência dos Gastos na Educação dos Municípios Goianos - Carlos Rosano-Peña; Pedro Henrique Melo Albuquerque; Cecílio Elias Daher (RAC: Revista de Administração Contemporânea, 2012)
In a context of scarcity and increased need for rationality in the use of municipal finances, there is increased relevance for school productivity and spending efficiency. This article seeks to assess the evolution of productivity in public spending on education in the municipalities of Goiás in the years 2005, 2007 and 2009, using the Malmquist Productivity Index combined with the method Data Envelopment Analysis (DEA) and the Markov Chains technique. The results reveal the improvement in productivity levels and its causes: changes in productive efficiency and technology. The results also show that if school systems maintain the dynamics presented in the analyzed period, the initial number of efficiency states (nine) must also be maintained. This tendency does not form closed classes, as all states are accessible and communicate with each other. However, the most efficient state is only one that grew over the long term. This occurs due to municipalities reducing their participation in other states. This should be a reflection of the productivity gain and rejects hypothesis of divergence trends in the evolution of efficiency. The results showed that the method can be an interesting alternative to evaluate the dynamic performance of public finances and decision-making support.